Strategy Analysis of the Public Works Office Public Works and Public Housing in the Construction of Special Road Transportation Mining from Mining Business Licensing in Jambi Province - Robby Septiandani; Ermaya Suradinata; Andi azikin (INFOKUM, 2025)
The purpose of this study is to analyze the Strategy of the Public Works and Public Housing Agency in the Development of Special Mining Transportation Roads from Mining Business Licensing in Jambi Province. The research method uses qualitative descriptive analysis, the study uses a purposive sampling method. Data and information collection, namely observation, interviews, and questionnaires. Data validation tests carried out by researchers are by using source triangulation techniques, technical triangulation, and time triangulation. The results of the study show that 1) the long licensing process often hampers implementation. Supervision and feasibility studies exist, but high costs for land acquisition are an obstacle. The involvement of the PUPR Agency in supervision is still lacking, and government support in complex licensing also needs to be improved. To maximize implementation, there needs to be increased socialization of the benefits of special roads, simplification of the licensing process with one-stop service, and a fair compensation scheme for the community. Improving coordination between agencies and holding regular discussion forums is also very important. 2) The challenges in implementing the strategy of building special mining roads by the Public Works and Public Housing Agency in Jambi Province include five indicators: Ability, Strength, Intelligence, Opportunity, and Culture. The most important aspect is the company's ability to find funding for this project, because the Jambi Provincial Government is not involved in funding, so all costs are borne by the private sector. This creates obstacles in the implementation of the construction of special coal roads.